2011
DOI: 10.1016/j.jemermed.2009.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Past-Year Intentional and Unintentional Injury Among Teens Treated in an Inner-City Emergency Department

Abstract: An inner-city Emergency Department (ED) visit provides an opportunity for contact with highrisk adolescents for promoting injury prevention.Objectives-To identify the prevalence of injuries sustained over the past year by teens presenting to an inner city ED, and to identify factors associated with recent injury to inform future ED-based injury prevention initiatives.Methods-Over one year, seven days a week, from 1:00-11:00 PM, patients ages 14-18 years presenting to the ED participated in a survey regarding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…A survey of youth presenting to an emergency department (ED), regardless of chief complaint, found that 9.6% reported sustaining a violent injury resulting in medical treatment in the past year. 48 A similar study of Reinjury healthcare costs þ perpetration victim healthcare costs þ perpetration criminal justice costs þ lost productivity costs Societal adults found that 11.0% reported being assaulted in the past year 49 and a study using Monitoring the Future survey data found a 1-year violent reinjury rate of 8.8% among high school students, 26 but the proportion of injuries resulting in hospital care was not reported in either study. Furthermore, this study focused on violent reinjury at 5-year follow-up and should be considered within the context of research that has assessed violent reinjury at different follow-up periods.…”
Section: Discussionmentioning
confidence: 97%
“…A survey of youth presenting to an emergency department (ED), regardless of chief complaint, found that 9.6% reported sustaining a violent injury resulting in medical treatment in the past year. 48 A similar study of Reinjury healthcare costs þ perpetration victim healthcare costs þ perpetration criminal justice costs þ lost productivity costs Societal adults found that 11.0% reported being assaulted in the past year 49 and a study using Monitoring the Future survey data found a 1-year violent reinjury rate of 8.8% among high school students, 26 but the proportion of injuries resulting in hospital care was not reported in either study. Furthermore, this study focused on violent reinjury at 5-year follow-up and should be considered within the context of research that has assessed violent reinjury at different follow-up periods.…”
Section: Discussionmentioning
confidence: 97%
“…Although death is the most severe consequence of violence, and homicide is the leading cause of death among African American adolescents (CDC 2009), nonfatal injuries are far more common. In 2007, more than 668,000 10-24 year olds in the United States were treated in emergency departments for injuries caused by violence (CDC 2009) and the ED is increasingly recognized as a important contact location for youth at risk for future violent injury (Cunningham et al 2011). In addition, a recent study surveying all youth presenting to an urban emergency department for any reason found that three quarters of adolescents reported recent peer violence (Walton et al 2009).…”
Section: Youth Violencementioning
confidence: 99%
“…Seven percent of the sample was Hispanic/Latino. This study is based on baseline self-administered survey data collected as part of a randomized control trial (RCT) of an emergency department intervention for alcohol use and violent (aggressive) behaviors (see Cunningham et al and Walton et al for more information) (Cunningham et al 2011;Walton et al 2010). To be selected to complete the baseline survey (and be enrolled in the study), participants had to endorse both past year aggression and alcohol consumption.…”
Section: Samplementioning
confidence: 99%
“…(1)(2)(3)(4)(5)(6)(7)(8)(9) Beyond the physical trauma, violence carries significant lifelong implications for psychosocial development as evidenced by increased psychological and behavioral problems. (3,5,6,10) Obtaining adequate psychosocial, educational, and physical health resources for survivors of violent injury is difficult and many victims return to stressful home environments, making their recovery even more complex.…”
Section: Introductionmentioning
confidence: 99%